Energy expenditure per minute in different activities and body positions and its association with the classification as physically active or inactive in daily life in individuals with COPD. (15th October 2021) - Brito, Igor L; Schneider, Lorena; Hirata, Raquel P; Fonseca, Juliana; Paes, Thais; Machado, Felipe VC; Rodrigues, Antenor; Hernandes, Nidia A; Pitta, Fabio
Objective: To describe and compare energy expenditure (EE)/minute walking and in different body postures in individuals with COPD; and to investigate if EE/minute walking is a predictor of their classification as physically active or inactive.Methods: Physical activity (PA) in daily life was objectively assessed using two PA monitors for 7 days and data were analyzed on a minute-by-minute basis. Predominant minutes were separated into walking, standing, sitting, and reclined, and EE/minute (a reflection of PA intensity) was then calculated in each of these four activities and postures. Participants were classified as active and inactive according to the criteria proposed by the American College of Sports Medicine (ACSM).Results: 43 individuals were evaluated (65±8 years; FEV1 50±14% predicted). A binary logistic regression model yielded that, regardless of the time spent walking/day, EE/minute walking was a significant predictor of the classification as physically active (OR=18.2 [2 – 165]; p =0.01), together with BMI (OR=0.68 [0.5 - 0.9]; p =0.008) (model: Chi-square = 22.431, p < 0.05; R 2 [Nagelkerke] = 0.556). In the active group, significantly higher EE/minute was observed for walking and standing in comparison both to sitting and reclined. However, in the inactive group, there were significant differences in EE/minute only when comparing walking versus reclined and standing versus reclined.Conclusion: In individuals, with COPD, EE/minute walking is a significant predictor of being classified as physically active, independently of the time spent walking/day. Each additional kilocalorie/minute spent walking increases in 18 times the chances to be classified as physically active in daily life.